Chemical site-selective prenylation of proteins. - Gamblin, D; van Kasteren, S; Bernardes, G; Chalker, J; Oldham, N; Fairbanks, A; Davis, B (2008)
A direct thionation procedure allows conversion of allylic alcohols into the corresponding thiols, the products of which are immediately compatible with one-pot site-selective selenenyl sulfide mediated protein conjugation.